Constructing and Reconstructing Motherhood. An Ethnografic Approach to Contemporary State Interventions Relating to Young Women in Greater Buenos Aires - Gaitán, Ana Cecilia (Universidad del Pacífico, 2015)
This article employs theoretical perspectives on the complex reconfigurations of state involvement in social life to explain some aspects of contemporary state interventions related to teenage pregnancy and motherhood. Employing an ethnographic approach, this study explores the ways that these types of interventions are carried out in a popular sector neighborhood of Greater Buenos Aires through territorialized state actions, which configure patterns of everyday intervention related to the sexual and reproductive health of these young people; this brings about not only tensions, but also contradictions.